Visualization investigation of the effects of nanocavity structure on pool boiling enhancement. (June 2019) - Hong, Sihui; Jiang, Siqiang; Hu, Yanxin; Dang, Chaobin; Wang, Shuangfeng
Graphical abstract: With visualization experiments of pool boiling on 3D nanostructured surfaces, bubble dynamics and heat transfer characteristics are both investigated. The dendritic nanostructured surface can not only reduce the initial temperature overshoot to 2.9 K at ONB, but also withstand more than 1.61 times the heat flux of the flat surface. The proposed high-performance and cost-effective nanostructured surface enables a reliable hydrophobic surface to be applied in electronics cooling, nuclear engineering, chemical, and petrochemical industries, etc . Highlights: Prepared two 3D nanostructured metallic surfaces with electrodeposition method. Characterized surface micro-morphology and hydrophobicity by SEM and contact angle. Explored the effect of 3D nanostructures on bubble dynamics with visualization method. Compared the pool boiling heat transfer enhancement in of these two surfaces. Summarized the heat transfer mechanisms induced by the difference of nanostructures. Abstract: Boiling heat transfer can be greatly enhanced through careful control of the physiochemical characteristics of contact surfaces. In this work, by utilizing the electrodeposition method, we prepared enhanced metallic surfaces with 3D cubic Cu2 O crystals and dendritic copper branch nanostructures. Their static contact angles are 127° and 139°, respectively. Additionally, incipience temperature overshoot at the onset of nucleate boiling decreased to only 4.4 K and 2.9 K from 15.3 K, and the maximum heat transfer coefficients for the conditioned surfaces were improved by 311.4% and 389.2%, respectively. Based on comparative analysis, the effects of nanocavity structure on bubble dynamics and heat transfer mechanisms are explicitly clarified. We determined that deep nanoscale cavities with interconnected branch structures are the key factor for facilitating appreciable capillary force and low seepage resistance to maintain efficient boiling heat transfer. Slender bubbles generated from dendritic structured surfaces effectively mitigate bubble coalescence and delay local vapor film coverage, thereby overcoming the defect of heat transfer deterioration under high heat flux. A surface with a 3D dendritic nanostructured layer can withstand a heat flux up to q = 73.53 W/cm 2 without drying out.